The metabolism of nonstructural carbohydrates, lipids, and energy in two Cycas species with differential tolerance to unexpected freezing stress - Wu, Yangyang; Zhu, Huan; Ling, Zhiwei; Lu, Erya; Peng, Xiaoling; Zheng, Yanling (Frontiers in Plant Science, 2023)
Introduction With the climate warming, the occurrence of freezing events is projected to increase in late spring and early autumn in the Northern Hemisphere. Observation of morphological traits showed that Cycas panzhihuaensis was more tolerant to unexpected freezing stress than C. bifida. Energy balance is crucial for plant tolerance to stress. Here, we aimed to determine whether the different responses of the two species to the unpredicted freezing stress were associated with the metabolism of energy and related substances. Methods The effects of unexpected freezing temperatures on C. panzhihuaensis and C. bifida were studied by measuring chlorophyll fluorescence parameters, energy charge and the profile of nonstructural carbohydrates (NSC) and lipids. Results C. panzhihuaensis exhibited higher stability of photosynthetic machinery than C. bifida under unpredicted freezing events. Significant interaction between species and treatments were observed in the energy charge, the level of NSC and its most components and the amount of most lipid categories and lipid classes. The decrease of soluble sugar and the increase of neutral glycerolipids at the early freezing stage, the accumulation of membrane glycerolipids at the late freezing stage and the continuous decrease of energy charge during the freezing period were the characteristics of C. panzhihuaensis responding to unexpected freezing stress. The degradation of membrane glycerolipids and the continuous decrease of soluble sugar during the freezing period and the accumulation of neutral glycerolipids and energy charge at the late freezing stage represented the characteristics of C. bifida responses. Discussion The different freezing sensitivity between C. panzhihuaensis and C. bifida might be associated with the differential patterns of the metabolism of energy, NSC and lipids. C. panzhihuaensis possesses the potential to be introduced to the areas of higher latitudes and altitudes.